Growth and productivity of lettuce cultivars under protected environment with and without thermal reflector screen - Gonçalves-Trevisoli, Edilaine Della Valentina; Dartora, Janaína; Mendonça, Heloísa Ferro Constâncio; Rissato, Bruna Broti; Dildey, Omari Dangelo Forlin; Coltro-Roncato, Sidiane; Santana, José Carlos de; Klosowski, Élcio Silvério; Echer, Marcia de Morais; Tsutsumi, Cláudio Yuji (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The aim of this work was to evaluate the growth and productivity of lettuce cultivars in greenhouse with and without thermo-reflective screens. The experiment was conducted in Assis Chateaubriand, Paraná State, Brazil. The experimental design was in randomized blocks, with six replications and treatments arranged in a 2 x 4 factorial. The first factor consisted of culture environments (with and without thermo-reflective screens 50%) and the second of four cultivars of lettuce (Itapuã, Paola, Vera and Verônica). Five samples were performed, weekly, for evaluation of dry matter and leaf area used to obtain the absolute and relative growth rates, net assimilation rates, leaf area ratio and specific leaf area. At the last evaluation were also determined: plant height, leaf number, canopy diameter, leaf and shoot fresh matter and productivity. The use of the thermo-reflective screens interfered on the development of lettuce promoting reduction in growth rates and the accumulation of fresh matter. The Paola cultivar did not present a good performance in the conditions of study. The use of thermo-reflective screens reduced the productivity of lettuce by 19% and did not correspond to the expected improvement on crop yield.